2005
DOI: 10.1017/s1461145705005389
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of 635 patients confirms an age-related association of the serotonin 2A receptor gene with tardive dyskinesia and specificity for the non-orofacial subtype

Abstract: Tardive dyskinesia (TD) is an important limiting factor in the use of typical antipsychotic drugs. Genetic variability in the serotonin 2A (5-HT(2A)) receptor may influence risk for TD but the results of prior studies are not confirmatory. The objective of this study was to determine association of T102C and His452Tyr polymorphisms in the 5-HT(2A) receptor gene (HTR(2A)) with TD in a large, multicentre patient sample. The design employed case-control analysis controlling for possible confounders using pooled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 68 publications
1
71
0
3
Order By: Relevance
“…Initial reports on association between 5-HT 2A polymorphisms and TD 224,243,244 were not replicated in independent studies. 205,247,246 The association was later confirmed in a combined analyses controlling for patients' age, 245 an important factor in the development of TD. Serotonin 5-HT 2C promoter polymorphisms were reportedly associated with TD.…”
Section: Prediction Of Side Effectsmentioning
confidence: 81%
“…Initial reports on association between 5-HT 2A polymorphisms and TD 224,243,244 were not replicated in independent studies. 205,247,246 The association was later confirmed in a combined analyses controlling for patients' age, 245 an important factor in the development of TD. Serotonin 5-HT 2C promoter polymorphisms were reportedly associated with TD.…”
Section: Prediction Of Side Effectsmentioning
confidence: 81%
“…Previously, other genes were included in meta-analyses such as (1) the gene encoding for 5-HT2A 82 (a) showing a small but significant association of the T102C genotype in several subgroups of TD and (b) the 5-HT2A His452Tyr polymorphism that showed a significant association with TD in a two-locus haplotype with T102C, (2) the joint comparison group of deficient alleles (*3, *4, *5) with TD 10 and (3) the gene encoding for DRD3 7,83 showed a significant excess of the Gly-allel and Gly-Gly homozygotes of the Ser9Gly polymorphism in patients with schizophrenia and TD. The meta-analysis of Bakker et al 7 showed a reduced or even opposite tendency in Asians compared to non-Asians.…”
Section: Resultsmentioning
confidence: 99%
“…51 The CATIE TD sample was based on prospective design with multiple evaluations per patients, whereas the retrospective Israeli study employed a cross-sectional design and patients were assessed for TD only once. 21,22,32,33 Therefore, a further consideration is the use of the potentially highly valuable extreme phenotype approach in this cohort sample. Because of the fluctuating nature of TD, and the fact that TD may be suppressed by increasing antipsychotics doses, it is possible that for some patients the classification may not be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…These include variants within COMT, DRD2, MnSOD, DRD3, HTR2A, CYP1A2 and CYP2D6. [21][22][23][24][25][26] Recently, two genomewide association studies (GWASs) and a large candidate gene study of TD were published, based on the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study, using two different definitions for TD phenotype. [27][28][29] Although none of the top results reached genome-wide significance, the association of single-nucleotide polymorphism (SNP) rs3943552 in the GLI2 gene with TD was observed in the CATIE sample and independently supported in Jewish Israeli schizophrenia patients of Ashkenazi origin.…”
Section: Introductionmentioning
confidence: 99%